Producing community pharmacy : complex performances in a hybrid space : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Albany, New Zealand - McGuigan, Kathryn Amy (Massey University, 2018)
Community pharmacies are recognisably hybrid health and retail spaces that are increasingly expanding beyond medicine-dispensing into new arenas of healthcare. However, there is limited understanding of the community pharmacy as a complex hybrid and socially-produced space. This thesis explores the community pharmacy as a hybrid, everyday and performative space using ethnographically-inspired methods to uncover the routines, performances and experiences within and across four pharmacies. Data was collected from two Life pharmacies and two Unichem community pharmacies using non-participant observation, mapping, photography, and interviews. Findings are presented in three parts, focussing on the landscape of the community pharmacy, staff practices, and customer performances in turn. The first findings chapter reveals that Life and Unichem pharmacies have distinctly different looks, ambience and feel that immediately identify them. However, all pharmacies had seven identifiably-distinct spaces: the dispensary, Over-the-Counter (OTC) medicines, Complementary and Alternative Medicines (CAM), the counter, the consulting room, beauty, and gifts. These spaces varied in size but were located in similar positions within each pharmacy, and each space was subject to its own boundaries and power differentials. The dispensary is the most powerful space, followed by OTC and CAM spaces, because of the symbolic power of medicine and health. The boundaries around the CAM space were blurred and precarious, illustrating how CAM is on the boundaries of orthodox medicine, but is important to the expanding arena of health in the pharmacy. The counter area is subject to competing powers vying for visual and commercial dominance in the pharmacy. The beauty and gifts spaces had gendered boundaries and although beauty spaces attempted to medicalise skin care, beauty was primarily seen as a retail necessity as well as a community service. The community pharmacy is more than a hybrid space, it is a site of multiple practices across and within seven distinct spaces. Exploring the physical and symbolic boundaries around and within these spaces illustrated how the community pharmacy meaning is comprised of movement and intersections across and within space. Exploring the spaces also revealed power differentials and competing stakeholders within the community pharmacy. Power played out within and across orthodox medicine, CAM, and beauty in aesthetics, symbols and physical aspects of the pharmacy such as marketing, product placement and staff hierarchies illustrating the complexity of the community pharmacy space. The second findings chapter explores professionalism, boundary work and interactions of community pharmacy staff in both the dispensary and the shop floor. Boundaries around the dispensary are demarcated and exclusionary. Technicians are limited to working in the dispensary with clearly-defined work boundaries. In contrast, the pharmacist works within the dispensary and on the shop floor and the different spaces require different performances but are both tied to the pharmacist’s professional identity. Pharmacy culture, expectations, the pharmacy brand, individual preferences and interests also influence professionalism and role boundaries of the pharmacist. For the pharmacist intern boundaries move and change as the performance moves from the dispensary to the shop floor. Retail staff play an important role in the social production of pharmacy. They have a range of performances from gatekeeping, sentry duty, and guiding customers in medicine, health, and beauty consultations. These staff use expertise developed with experience and on-the-job training to claim a conditional expert status, particularly in the medicines spaces such as OTC and CAM. The power of medicine functions to marginalise beauty staff keeping them on the boundaries of the pharmacy physically and symbolically. The analysis further revealed that emotional labour was required by all staff to create a sense of community in the pharmacy. Different spaces and different products required different emotional labour, with marked differences between health and beauty interactions. The boundary work and emotional labour of all staff reflects and reinforces the dominant medical, professional and gender hierarchies that are operative, highlighting the interwoven nature of space and staff practices in the community pharmacy. The final findings chapter explores the range of customer experiences within the community pharmacy. Customers’ performances were driven by consumption of health and non-health purposes but also by the nature of the pharmacy space itself. There were distinct differences between health and non-health practices. Health consumption involved the use of boundary objects, such as the prescription, and rituals to seek health advice, products and service such as displaying symptoms and storytelling. Filling a prescription revealed interesting differences across its three distinct phases (handing in, waiting and collecting). Handing in the prescription was consistent across pharmacies and customers, whereas waiting practices were gendered. Collecting the prescription was more complicated, and differed from pharmacy to pharmacy, leading to customer uncertainty. Non-health consumption was gendered due to the products on offer, and this was sustained by the feminine aesthetic of the beauty and gift spaces. Overall, customers were found to be active consumers who embrace the hybrid functions of the pharmacy, assimilating, modifying and rejecting health and non-health products, information and advice. The closing chapter offers a discussion, drawing on performativity, to consider how staff and customers interact with space, people and products to create the social production of pharmacy. Customers use the community pharmacy as a hybrid site of health and retail, using strategies and tactics to incorporate, modify and reject dominant health and beauty ideologies and discourses. Pharmacy staff are more constrained by spatial and role boundaries in both health and non-health spaces, but use emotional labour and patient-centred practices to create a relational and community space. Overall, this research highlights that the community pharmacy is a dynamic, relational and complex space.
Keywords: Drugstores; Social aspects; New Zealand; Pharmacists; Drugstore employees; Consumer behavior; Performative (Philosophy); Spatial behavior